Proveniência dos sedimentos de porção aflorante do membro Angico, Formação Riachuelo, da sub-bacia de Sergipe - Santos, André Alves dos (2015)
The Sergipe-Alagoas Basin has one of the most complete stratigraphic succession of eastern and southeastern shores of Brazil. In Sub-basin of Sergipe the Riachuelo Formation occurs in the namesake city in Sergipe, about 30 km Northwest of the state capital. This formation register the first sediments deposited under marine conditions and is subdivided into three members: Angico, Taquari and Maruim. These rocks are an example of sedimentation related to the drift phase, during the opening of the South Atlantic Ocean. In this work we obtained U-Pb isotopic data (LA-ICP-MS) of 82 detrital zircon grains, from two samples of sandstones belonging to the Angico Member. They indicate five main groups age intervals, suggesting the following sources: G1 [901 Ma to 1152 Ma - 11%] Orogenic System Sergipe (Borborema Province); G2 [1439 Ma to 1508 Ma - 4%] Borborema Province and São Francisco Craton; G3 [1762 Ma to 2467 Ma - 27%] Serrinha Nucleus (Craton); G4 [2603 Ma to 2892 Ma - 30%] Serrinha Nucleus (São Francisco Craton); and G5 [2953 Ma to 3468 Ma - 28%] Serrinha Nucleus (São Francisco Craton). The majority of the ages obtained (85%) are paleoproterozoic to paleoarqueanas, and probably, the Serrinha Nucleus (Craton) was the main source area for the sediments of the Angico Member.